Effects of glutamine and hyperoxia on pulmonary oxygen uptake and muscle deoxygenation kinetics - Marwood, S.; Bowtell, J. L. (European Journal of Applied Physiology, 2007)
The aim of the present study was to determine whether glutamine ingestion, which has been shown to enhance the exercise-induced increase in the tricarboxylic acid intermediate (TCAi) pool size, resulted in augmentation of the rate of increase in oxidative metabolism at the onset of exercise. In addition, the potential interaction with oxygen availability was investigated by completing exercise in both normoxic and hyperoxic conditions. Eight male cyclists cycled for 6 min at 70% \mathop V· \textO2max VO2maxfollowing consumption of a drink (5 ml kg body mass-1) containing a placebo or 0.125 g kg body mass-1 of glutamine in normoxic (CON and GLN respectively) and hyperoxic (HYP and HPG respectively) conditions. Breath-by-breath pulmonary oxygen uptake and continuous, non-invasive muscle deoxygenation (via near infrared spectroscopy: NIRS) data were collected throughout exercise. The time constant of the phase II component of pulmonary oxygen uptake kinetics was unchanged between trials (CON: 21.5 ± 3.0 vs. GLN: 18.2 ± 1.3 vs. HYP: 18.9 ± 2.0 vs. HPG: 18.6 ± 1.2 s). There was also no alteration of the kinetics of relative muscle deoxygenation as measured via NIRS (CON: 5.9 ± 0.7 vs. GLN: 7.3 ± 0.8 vs. HYP: 6.5 ± 0.9 vs. HPG: 5.2 ± 0.4 s). Conversely, the mean response time of pulmonary oxygen uptake kinetics was faster (CON: 33.4 ± 1.2 vs. GLN: 29.8 ± 2.3 vs. HYP: 33.2 ± 2.6 vs. HPG: 31.6 ± 2.6 s) and the time at which muscle deoxygenation increased above pre-exercise values was earlier (CON: 9.6 ± 0.9 vs. GLN: 8.7 ± 1.1 vs. HYP: 8.5 ± 0.8 vs. HPG: 8.4 ± 0.7 s) following glutamine ingestion. In normoxic conditions, plasma lactate concentration was lower following glutamine ingestion compared to placebo. Whilst the results of the present study provide some support for the present hypothesis, the lack of any alteration in the time constant of pulmonary oxygen uptake and muscle deoxygenation kinetics suggest that the normal exercise induced expansion of the TCAi pool size is not limiting to oxidative metabolism at the onset of cycle exercise at 70% [(V)\dot]O2 max.VO2max